2015
DOI: 10.17557/.36557
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fertilization and Grazing Applications on Root Length and Root Biomass of Some Rangeland Grasses

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Grazing affects plant growth, degrades the physical structure of soil, and reduces water permeability of soil, thereby affecting soil spatial distribution (Chen et al, 2013 ; Liu, Lü, et al, 2018 ; Yavuz & Karadag, 2015 ). Studies have shown that plants can preferentially find nutrients in “exotic” soil patches in spatially heterogeneous soils, which may reduce imbalance of inter‐species competition (Hendriks et al, 2015 ; Xue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Grazing affects plant growth, degrades the physical structure of soil, and reduces water permeability of soil, thereby affecting soil spatial distribution (Chen et al, 2013 ; Liu, Lü, et al, 2018 ; Yavuz & Karadag, 2015 ). Studies have shown that plants can preferentially find nutrients in “exotic” soil patches in spatially heterogeneous soils, which may reduce imbalance of inter‐species competition (Hendriks et al, 2015 ; Xue et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, grazing disturbance influences seed availability for seedling emergence by affecting seed production and seed distribution in soil; for instance, research showed that total seed density and species richness in the soil seed bank was higher in grazed grassland than in enclosed grassland (Zuo et al, 2013). On the other hand, grazing alters the habitats on which seedling emergence and survival rely, such as soil compaction, water permeability, and holding capacity (Oesterheld & Sala, 1990; Osem et al, 2006; Taddese et al, 2002; Yavuz & Karadağ, 2015). The changes in seed availability and environmental factors further cause the difference in seedling number, richness and composition, and determine seedling growth and survival (Schuster et al, 2016).…”
Section: Introductionmentioning
confidence: 99%